State Accountability and the Problem of Citizen Lawsuit Execution - Triwanto, Triwanto; Wulakada, Imam Al Ghozali Hide (Universitas Muhammadiyah Purwokerto, 2026)
This article examines state accountability and the weak execution of Citizen Lawsuit decisions in Indonesia’s public service context. Using a normative juridical method with statutory, conceptual, and comparative approaches, the study analyzes constitutional and legislative obligations regarding public services and road infrastructure, as well as their enforcement through Citizen Lawsuits. The findings show structural and normative problems: ambiguity of legal forum (civil or administrative courts), absence of clear execution norms, and predominantly declaratory judgments without coercive mechanisms. These weaknesses create a gap between formal recognition of state negligence and the actual restoration of citizens’ rights. Comparative insights from the United States, India, and theoretical discussions on the rule of law and anti-corruption indicate that effective enforcement design is crucial to strengthening public trust and accountability. The article proposes reform of legal norms, procedures, and institutional coordination to ensure that Citizen Lawsuit decisions are executable and provide substantive protection.